Working Posture and Low Back Pain among Female Home Convection Workers: A Cross-Sectional Study - Harahap, Aletta Khaerunnisa Putri; Ghozali, Dhoni Akbar; Munawaroh, Siti; Handayani, Selfi; Hastami, Yunia (Universitas Muhammadiyah Yogyakarta, 2024)
Low back pain (LBP) is a significant contributor to global musculoskeletal disorders, often associated with uncomfortable working postures prevalent among home convection workers. This study investigates the correlation between work posture and LBP incidence in 36 female home convection workers aged 20-55, selected through total sampling. This study employed an analytical observational design with a cross-sectional approach. Conducted from March 31 to June 17, 2023, in Sragen, the study utilized RULA with an ordinal scale for posture analysis and the Modified ODI questionnaire, also employing an ordinal scale for LBP measurement. Results revealed 52.78% with low-risk and 47.22% with high-risk postures. Most LBP cases were mild (35 individuals). Kendall’s tau correlation test showed no significant relationship between work posture and LBP incidence (p-value = 0.175, p 0.05). This research concluded that there was no significant relationship between work posture and the incidence of LBP among female home construction workers. However, no significant correlation was found; 47.22% faced a high risk of other musculoskeletal disorders, highlighting the need for immediate posture changes among these workers.